Graphics Reference
In-Depth Information
α ( μ, r +1)= β 1 ;
μ 2= μ 2
1;
end
One can also use an alternative algorithm to compute d ( j ) as given by
equation (7.29). Now, before we describe the algorithmic steps, we first con-
sider the underlying background of it. By equation (7.25),
μ
d ( j )=
α i,k ( j ) P i
i = μ−k +1
μ
=
[( t j + k− 1
τ i ) β i,k− 1 ( j )+( τ i + k
t j + k− 1 ) β i +1 ,k− 1 ( j )] P i .
i = μ
k +1
Since β μ−k +1 ,k− 1( j )= β μ +1 ,k− 1 ( j ) = 0 by (1) in the corollary, we get,
μ
α i,k− 1 ( j ) P [2]
d ( j )=
i,j ,
i = μ
k +2
where
P [2]
i,j
=[( t j + k− 1
τ i ) P i +( τ i + k− 1
t j + k− 1 ) P i− 1 ] / ( τ i + k− 1
τ i ) .
In general, for r =1 , 2 ,
···
,k ,
μ
α i,k−r +1 ( j ) P [ r ]
d ( j )=
i,j ,
i = μ
k + r
with
P [1]
i,j
= P i
and
P [ r +1]
i,j
τ i ) P [ r ]
t j + k−r ) P [ r ]
=[( t j + k−r
i,j +( τ i + k−r
1 ,j ] / ( τ i + k−r
τ i ) .
i
Therefore, when r = k ,wehave
d ( j )= α μ, 1 ( j ) P [ k ]
μ,j
= P [ k ]
μ,j .
With this, we write down Algorithm 2 to compute d ( j ).
Algorithm 2:
Step 1: μ 2= μ
k +1;
Step 2: for i = μ 2 2 +1 ,
···
do
begin
P [1 i = P i ;
Step 3: for r =1 , 2 ,
···
,k
1do
Search WWH ::




Custom Search